Comparative effects of propofol vs dexmedetomidine on cerebrovascular carbon dioxide reactivity in patients with septic shock - Kadoi, Y.; Saito, S.; Kawauchi, C.; Hinohara, H.; Kunimoto, F. (British journal of anaesthesia : BJA, 2008)
The use of sedative drugs is reportedly related to altered cerebrovascular CO2 reactivity. The present study examined the comparative effects of propofol vs dexmedetomidine on cerebrovascular CO2 reactivity in patients with septic shock. A total of 20 patients with septic shock who required mechanical ventilation were included in this study. Sedation during mechanical ventilation was maintained using either propofol or dexmedetomidine. A 2.5 MHz pulsed transcranial Doppler probe was attached to the head of the patient at the right temporal window for continuous measurement of mean blood flow velocity in the middle cerebral artery (Vmca). After establishing baseline values of Vmca and cardiovascular haemodynamics, end-tidal CO2 was increased by decreasing ventilatory frequency by 5–8 bpm. The absolute and relative CO2 reactivity values in patients with septic shock were lower for both propofol and dexmedetomidine than those for control groups, with significant differences between these values in the two septic shock groups (absolute CO2 reactivity in septic shock under propofol: 2.6 (sd 0.3) cm s−1 mm Hg−1; absolute CO2 reactivity in septic shock under dexmedetomidine: 2.0 (0.3) cm s−1 mm Hg−1; P<0.01). This study showed that cerebrovascular CO2 reactivity was lower under dexmedetomidine sedation than under propofol sedation during almost identical sedation in patients with septic shock.